Near‐Infrared Light Activated Thermosensitive Ion Channel to Remotely Control Transgene System for Thrombolysis Therapy. Issue 27 (15th May 2019) - Zhang, Da; Zhang, Cuilin; Lan, Shanyou; Huang, Yanbing; Liu, Jingfeng; Li, Juan; Liu, Xiaolong; Yang, Huanghao
Abstract: Current antithrombotic therapeutic strategies often suffer from severe post‐thrombotic syndromes (PTS), inconvenient daily subcutaneous injections for a long time and short circulation times accompanied by a dose‐dependent risk of intracranial hemorrhage. Aiming at noninvasive, on‐demand, and sustained antithrombotic therapy, a new thrombolysis approach based on the transgene system has been developed to remotely and precisely control the expression of urokinase plasminogen activator (uPA) by bioengineered cells for antithrombotic therapy both in vitro and in vivo. In this design, the near‐infrared (NIR) light could activate the expression of the thermosensitive TRPV1 channel in response to photothermal responsive nanotransducers to trigger the synthetic signaling pathway to secret uPA. By encapsulating bioengineered cells in injectable hydrogel to ensure long‐term survival and convenience for injection, the engineered cells could noninvasively and precisely control the production of uPA protein in situ via an NIR laser to significantly enhance the thrombolysis therapeutic effects by spatiotemporally controlling the local temperature, in both the microfluidic blood circulation mimic and the murine tail thrombus model. This novel thrombolysis approach could overcome some key limitations that are associated with conventional antithrombotic therapy, thus opening a new direction for developing remotely and precisely controllable continuous thrombolysis through artificially designed signaling. Abstract : Herein, a noninvasive and on‐demand bioengineered cell‐based approach to remotely and precisely control urokinase plasminogen activator production for thrombolysis therapy in vitro and in vivo by near‐infrared light OFF/ ON switching thermosensitive ion channel with the aid of photothermal responsive nanomaterials is reported.